Pengaruh Sosialisasi Pelayanan Pajak, Kualitas Pelayanan Pajak Dan Kesadaran Pajak Terhadap Kepatuhan Wajib Pajak Badan - Paulus Agut; Florentina Anjeli; Gusti Dian Prayogi (Jurusan Akuntansi Politeknik Negeri Padang, 2023)
This study aims to determine the effect of the level of taxpayer compliance including socialization of tax services, quality of tax services and tax awareness at KPP PRTAMA BOJONOGORO. The formulation of the problem in this study is whether the influence of the x and y variables has the same positive effect. The research results are useful for interested parties, namely KPP Pratama Bojonegoro, especially for taxpayers to fulfill taxpayer compliance. The results of this study state that socialization of tax services (X1), quality of tax services (X2) and taxpayer awareness (X3) have a significant positive effect on taxpayer compliance (Y). Socialization of tax services (X1) on taxpayer compliance (Y) has the coefficient value is positive by 0.226, the quality of tax services (X2) on taxpayer compliance (Y) has a positive coefficient value of 0.246, while the taxpayer awareness (X3) on taxpayer compliance (Y) has also a positive coefficient value of 0.336 Thus the hypothesis which states that